2021
DOI: 10.2147/orr.s309210
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Free Radical Stabilization Techniques on in vivo Mechanical Changes in Highly Cross-Linked Polyethylene Acetabular Liners

Abstract: Introduction Numerous thermal free radical stabilization techniques are used in the production of highly cross-linked polyethylene (HXLPE) to improve oxidative stability. Little knowledge exists on the effects of in vivo time on the mechanical properties of HXLPE. The purpose of this study was to determine if free radical stabilization of HXLPE impacts mechanical properties as well as oxidative stability of acetabular liner rims after extended in vivo time. Methods Retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…These findings are consistent with current literature which supports remelted liners exhibiting a lower overall crystallinity, which is associated with lower yield strength and fatigue resistance but less susceptibility to in vivo oxidation. 13,39,40 Similar to prior work by Decker et al, 34 higher overall rim subsurface microhardness was shown to be present in both singleannealed and sequentially annealed liners, with the single-annealed group exhibiting the highest values among the three groups. Previous studies have demonstrated that changes in hardness correlate with the extent of oxidation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings are consistent with current literature which supports remelted liners exhibiting a lower overall crystallinity, which is associated with lower yield strength and fatigue resistance but less susceptibility to in vivo oxidation. 13,39,40 Similar to prior work by Decker et al, 34 higher overall rim subsurface microhardness was shown to be present in both singleannealed and sequentially annealed liners, with the single-annealed group exhibiting the highest values among the three groups. Previous studies have demonstrated that changes in hardness correlate with the extent of oxidation.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, our study selected eight liners that exhibited the highest subsurface oxidation indices (OI) based on Fourier transform infrared spectroscopy (FTIR) testing in prior work. 34 These included two remelted, three single annealed, and three sequentially annealed liners. Each of these sample liners was sectioned with a Japanese Dozuki detail saw and polished by hand to maintain low processing temperatures to improve the accuracy of the microidentation interpretation.…”
Section: Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the formation of free radicals during the process of irradiation, which are responsible for continuing long-term oxidation reactions thus limiting the service life of UHMWPE. In order to stabilize the radiation-induced free radicals, number of methodologies are adopted including post irradiation annealing, melting, incorporation of bio-compatible of anti-oxidants, i.e., α-tocopherol (vitamin E) [ 9 , 10 , 11 ], irradiating the UHMWPE in the presence of predetermined amount of organo-silane [ 6 , 12 , 13 , 14 , 15 ], using the suitable silane-based clay [ 16 ], and preparing the UHMWPE nano composites with MWCNTs for quenching the radiation-induced free radicals [ 7 , 8 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%